Komunikasi Self-Disclosure Pasangan Pacaran Jarak Jauh dalam Memelihara Hubungan Serius Menuju Pernikahan pada Dewasa Awal di Surabaya - Syahputri, Puspita Dewi; Prima, Edelweis Puti (LPPM Stikosa-AWS, 2024)
In the phase of life, a person inevitably experiences the adult phase. Dating relationships lived by early adulthood lead to marriage. Self Disclosure affects the continuity of the romantic relationship established by both of them to be good. The purpose of this research is to find out how Self Disclosure of long-distance dating couples in maintaining a serious relationship towards marriage in early adulthood in Surabaya. This research used a qualitative approach descriptive method using Purposive Sampling technique. The subjects in this study were early adults who experienced long-distance courtship as many as six people. The results of the study were obtained based on the five dimensions of Self Disclosure, all informants have diverse answers and self-management in maintaining their relationships. All informants have made self-disclosure to their partners so that they can maintain their relationships. Although there are informants who are not fully exposed. In this study, the use of communication media used was whatsapp. The obstacle they experience is signal interference in one of their partner's places.